A Descriptive Study of Code-Mixing in “My Stupid Boss Part 1” Movie - Sendi Wahyuni; Wulan Wangi; Wageyono (LUNAR, 2021)
Nowadays, code-mixing phenomenon is commonly used in communication. In this case, people sometimes mix the language into another language in order to get understand and succesful of communication. The objectives of the study are to find out the types and the levels of code-mixing used in “My Stupid Boss part 1” movie. In this study, the researcher focuses on Indonesian, English, and Javanese utterance. This research method used a descriptive qualitative method. It described the results of research that was objectively analyzed by collecting data. The data source was script movie. The researcher used free listening method. Then, the analysis method followed the steps of Miles and Hubarman. The result was displayed on the table of code-mixing and explained with narrative text. The researcher used 58 data from the utterances in the movie that are considered is able to represent of code-mixing. Analysis focused on two types and six levels of code-mixing. There are 12 of inner code-mixing and 54 of outer code-mixing used in this movie. Then, there are 40 of word levels, 18 of phrase levels, 2 of clause levels, 1 of baster level, and 7 of repetition word level.